2018
DOI: 10.1039/c8dt01631c
|View full text |Cite
|
Sign up to set email alerts
|

Covalently linking CuInS2 quantum dots with a Re catalyst by click reaction for photocatalytic CO2 reduction

Abstract: Covalently linking photosensitizers and catalysts in an inorganic-organic hybrid photocatalytic system is beneficial for efficient electron transfer between these components. However, general and straightforward methods to covalently attach molecular catalysts on the surface of inorganic semiconductors are rare. In this work, a classic rhenium bipyridine complex (Re catalyst) has been successfully covalently linked to the low toxicity CuInS quantum dots (QDs) by click reaction for photocatalytic CO reduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 66 publications
1
42
0
Order By: Relevance
“…Here, we will mainly focus on how the unique properties of QDs and the interaction between QDs and cocatalysts would promote CO 2 photoreduction. Table 1 gave a detailed summary of the currently reported examples of utilization of QDs for CO 2 photoreduction . The recent advances of using semiconductor QDs in photocatalytic CO 2 reduction will be discussed in three categories: II–VI QDs, I–III–VI QDs and perovskite‐type QDs.…”
Section: Semiconductor Qds For Photocatalytic Co2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we will mainly focus on how the unique properties of QDs and the interaction between QDs and cocatalysts would promote CO 2 photoreduction. Table 1 gave a detailed summary of the currently reported examples of utilization of QDs for CO 2 photoreduction . The recent advances of using semiconductor QDs in photocatalytic CO 2 reduction will be discussed in three categories: II–VI QDs, I–III–VI QDs and perovskite‐type QDs.…”
Section: Semiconductor Qds For Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…Recently, a cocatalyst of rhenium bipyridine complex (Re catalyst) had been covalently linked to the surface of CuInS 2 QDs by Click reaction ( Figure a) . Ultrafast TA spectroscopic analysis showed that the surface binding Re cocatalyst could quickly acquire an electron from the excited QDs within 300 fs (Figure b).…”
Section: Semiconductor Qds For Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…[ 189–191 ] Because of the narrow bandgap (≈1.50 eV) and favorable photoabsorption (Figure 25d), CuInS 2 was developed to be a great potential and sustainable catalyst candidate in photocatalysis for H 2 evolution, CO 2 reduction, and degradation of pollutants. [ 192–195 ]…”
Section: Ternary Metal Sulfide Photocatalystsmentioning
confidence: 99%
“…Therefore, this concept could be applied to many combinations of photoactive semiconductors and metal‐complex catalysts. Several reports have indicated that the activity for CO 2 reduction could be improved by changing the photoactive semiconductor and metal‐complex catalyst [2–7] . Consequently, selective CO 2 reduction that utilizes only water and sunlight with water oxidation catalysts was successfully achieved using the hybrid photocatalysts concept [8–13] …”
Section: Introductionmentioning
confidence: 99%
“…Severalr eports have indicated that the activity for CO 2 reduction could be improved by changing the photoactive semiconductor and metal-complex catalyst. [2][3][4][5][6][7] Consequently,s elective CO 2 reductiont hat utilizes only water and sunlight with water oxidation catalysts was successfully achieved using the hybrid photocatalysts concept. [8][9][10][11][12][13] Time-resolved transientabsorption,e mission (TR-EM), and infrared absorption (TR-IR) spectroscopies are useful techniques for understanding fundamental photophysical and photochemicalp rocesses such as electron transfer.…”
Section: Introductionmentioning
confidence: 99%